Comparative Study of Plug and Abandonment Using Balanced Plug Cementing Method: Case Study of Well “NV-01” Field “NS” - Suhascaryo, KRT. Nur; CIIQA, CIIQA; Mama Anugrah, Andi Novita (Testing Center for Oil and Gas LEMIGAS, 2023)
The NOV-01 well is a directional well that has technical problems (fish), namely the stuck pipe problem and the problem of high land use operational costs. Based on the results of the evaluation of the economic and risk technical aspects, a plug & abandonment (P&A) was carried out for the NOV-01 well. The purpose of this research is to compare the 3 stages and 5 stages in P&A work and their influence on work program planning and budgeting. The research methodology is qualitative and quantitative. The NOV-01 well plug & abandonment activity is carried out by preparing a work program plan such as determining the depth interval of the well to be plugged, the volume of cement slurry & additives, as well as the rig method which all refer to the existing standards and regulations, namely SNI 13-6910-2002 and NORSOK D-010. The results of a comparative study on P&A planning at 3 stages required 279 sacks of cement and 450 sacks of cement at 5 stages with a density of 15.8 ppg. P&A on well NOV-01 uses the rig method with a capacity of 450 HP. For 3 stages it takes 9 days and 5 stages for 11 days. Comparison of estimated costs for P&A of NOV-01 well, namely 3 stages of IDR 6,062,977,890.31- and 5 stages of IDR 8,374,824,218.62-. Well NOV-01, P&A which is suitable is 5 stages because there is an overpressured zone so that the cement plug is isolated.